(untitled) (Metallurgy and Foundry Engineering, 2017)
The main aim of this study was to determine the influence of SiC particle size on the mechanical properties of aluminum matrix composites. The reinforcing phase was introduced into the aluminum matrix in two different particle sizes: a coarse fraction with particle size ranging from 40 to 60 μm, and a fine fraction with particle size of less than 2 μm. The SiC particles were added in various quantities equal to 2.5, 5, 7.5, and 10 wt% in order to determine the influence of different contents of the reinforcing phase on the density, hardness, and compressive strength of the obtained composite materials. By using scanning electron microscopy (SEM), the microstructure observations were performed and allowed for defining the influence of matrix/reinforcement particle size ratio (PSR) on the distribution of reinforcement particles in the matrix. The Al-SiC composites were prepared through the conventional powder metallurgy technique, including compaction under a pressure of 300 MPa and a sintering process in a nitrogen atmosphere at 600°C. Applying the reinforcing phase with the particle size (40–60 μm) similar to matrix (<63 μm) allowed us to obtain a more-uniform distribution of SiC particles in the matrix than after introducing the fine fraction of reinforcement (2 μm). The mechanical properties of the Al-SiC composites increased with increases in the weight fraction of the reinforcing phase, wherein this effect is more visible for composites reinforced with SiC particles of finer gradation.